Charlie Chaplin's The great dictator - Willson, Meredith 1902-1984 (The Criterion collection, 2011)
In Chaplin's first talkie, he plays the duel role of dictator Adenoid Hynkel and a Jewish barber who is a dead-ringer look-alike for der Nutsie...and who thwarts his plans for world domination